2022
DOI: 10.3390/cells11182872
|View full text |Cite
|
Sign up to set email alerts
|

Notch3 Transactivates Glycogen Synthase Kinase-3-Beta and Inhibits Epithelial-to-Mesenchymal Transition in Breast Cancer Cells

Abstract: As a critical transformational process in the attributes of epithelial cells, epithelial-to-mesenchymal transition (EMT) is involved in tumor invasion, metastasis, and resistance to treatment, which contributes to the ultimate death of some patients with breast cancer. Glycogen synthase kinase-3-beta (GSK3β) is thought to be an EMT suppressor that down-regulates the protein, snail, a zinc finger transcription inhibitor, and regulates E-cadherin expression and the Wnt signaling pathway. Our previous studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Here, we establish, for the first time to our knowledge, a signaling axis requiring the functions of RPSA upstream of SNAIL. Pertinent to our study, Notch3 was found to transactivate GSK3β and to inhibit EMT in a breast cancer cell model [ 50 ]. GSK3β regulates EMT and CSC properties in triple-negative breast cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 54%
“…Here, we establish, for the first time to our knowledge, a signaling axis requiring the functions of RPSA upstream of SNAIL. Pertinent to our study, Notch3 was found to transactivate GSK3β and to inhibit EMT in a breast cancer cell model [ 50 ]. GSK3β regulates EMT and CSC properties in triple-negative breast cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 54%
“…Previously, it has been reported that the expression of NOTCH3 is positively correlated with a lower Ki-67 index and the incidence of involved lymph node status in breast cancer patients, and predicts a better recurrence-free survival rate of breast cancer patients 38 . In addition, NOTCH3 up-regulates the expression of GSK3β, which is related to better recurrence-free survival rate of all breast cancer patients 14 . NOTCH3 is very weakly expressed in breast cancer cells, which prevents tumor occurrence through HeyL-mediated inhibition of Mybl2 (an important cell cycle regulator), and is related to good prognosis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In the NOTCH signaling pathway, when a ligand (DLL1、DLL3、DLL4、Jagged1 and Jagged2) binds to a NOTCH receptor (NOTCH1-4), it induces the release and nuclear translocation of NOTCH receptor intracellular domain (NICD), which interacts with the transcription factor CSL, leading to the transcriptional activation of its target genes. Different from the oncogenic role of NOTCH1/2/4 in breast cancer, which promotes the transformation of ductal carcinoma in situ to invasive breast cancer [11][12][13], NOTCH3 is considered to be a tumor suppressor in breast cancer [14,15]. In breast cancer cells, NOTCH3 can activate the Hippo/YAP pathway by up-regulating Kibra, thereby inhibiting EMT [16], and NOTCH3 inhibits EMT in breast cancer by transcriptionally up-regulating the expression of GATA-3 [17], suggesting that NOTCH3 inhibits the progression of breast cancer mainly through transcriptional activation of downstream target genes.…”
Section: Introductionmentioning
confidence: 99%